Analysis of Middle School Students' Learning Styles for Differentiated Learning in Mathematics Lessons - Azi Nugraha; Erlinda Isulis Marissa; Elly Rizeqia Fadilah (RANGE: Jurnal Pendidikan Matematika, 2024)
The aim of this research is to obtain a description of students' learning styles in studying mathematics. Learning style questionnaires and in-depth interview methods were used in this qualitative descriptive research design. Thirty class VIII students from one of the middle schools in Majalengka Regency were used as research subjects. An interview guide and a Google form-based learning style questionnaire were used as research instruments. The data analysis approach used is data reduction, data presentation, and drawing conclusions. The results of the analysis show that 17% of Class VIII students in one of the middle schools in Majalengka Regency have a kinesthetic learning style, 53% have a visual learning style, and 30% have an auditory learning style. These findings indicate that the visual learning style is the most common type of learning. To develop differentiated learning, teachers and schools must consider the different learning styles and needs of students.